Rainwater Harvesting (RWH) installation for buildings : a systematic review and meta-analysis approach / Azirah Adnan, Asmalia Che Ahmad and Suharto Teriman - Azirah, Adnan; Asmalia, Che Ahmad; Suharto, Teriman (Universiti Teknologi MARA, Perak, 2019)
Rainwater that falls upon a roof surface which are collected and transferred to the storage facility for later use is a method known as Rainwater Harvesting (RWH). This method is a step towards conserving the public drinking water where the demand continues to grow worldwide. In Malaysia, there is a huge potential of rainwater harvesting based on the available rainfall amount. Even so, the existing RWH design guideline in Malaysia lacks the technical specification regarding congruousness of RWH installation method with the physical characteristic of the building. Therefore, systematic literature review and meta-analysis were done to identify and understand the suitability between the types of RWH installation system with the building’s physical characteristic. The main objective of this study is to review the existing articles from year 2000 to the present on the installation systems used in RWH for non-potable purposes. The RWH installation system, types of building and building characteristics used in the previous studies will be evaluated in order to understand the suitability or regularity of the combinations. This review uses the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) as reviewing method. The systematic review process involved four stages which are identification, screening, eligibility and included. The sources of this review are Science Direct and Google Scholar. Results show there are three types of RWH installation system that were identified namely Gravity Fed System (GFS), Indirect Pumping System (IPS) and Direct Pumping System (DPS). DPS is commonly applied for non-potable purposes in residential, commercial and educational buildings. Small yard area, sloping site condition and types of soft landscape will affect the type of RWH installation system to be used. The result can be used to determine the suitability of the RWH installation system for different types and characteristics of a building.